2017
DOI: 10.1177/0954406217750189
|View full text |Cite
|
Sign up to set email alerts
|

Three driven approaches to combinational creativity: Problem-, similarity- and inspiration-driven

Abstract: Creativity is a crucial element of design. The aim of this study is to investigate the driving forces behind combinational creativity. We propose three driven approaches to combinational creativity, problem-, similarity-, and inspiration-driven, based on previous research projects on design process, strategy, and cognition. A case study involving hundreds of practical products selected from winners of international design competitions has been conducted to evaluate the three approaches proposed. The results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 69 publications
(118 reference statements)
1
34
0
Order By: Relevance
“…A number of studies have shown positive results of using samples from the winners of design awards. For example, the winning formulas for metaphor design (Wang, 2016), the 77 evidence-based design heuristics (Yilmaz et al, 2016), the three-driven approaches of combinational creativity (Han et al, 2019), and the conceptual distances in combinational creativity (Han et al, 2018b). Design competitions might lack rigorous creativity evaluations, but Wang and Chan (2010) indicted design competitions are creativity-oriented.…”
Section: Case Study Methodsmentioning
confidence: 99%
“…A number of studies have shown positive results of using samples from the winners of design awards. For example, the winning formulas for metaphor design (Wang, 2016), the 77 evidence-based design heuristics (Yilmaz et al, 2016), the three-driven approaches of combinational creativity (Han et al, 2019), and the conceptual distances in combinational creativity (Han et al, 2018b). Design competitions might lack rigorous creativity evaluations, but Wang and Chan (2010) indicted design competitions are creativity-oriented.…”
Section: Case Study Methodsmentioning
confidence: 99%
“…For instance, Bacciotti et al (2016) came up with a computational approach of combining concept from different dimensions to identify scenarios of products; Georgiev et al (2017) indicated a computational method of generating new scenes through the synthesis of existing scenes to support new product develop; Han et al (2018a) explored an approach imitating aspects of human cognition in producing combinational creativity, and came up with a computational ideation support tool named the Combinator; Chen et al (2018) demonstrated an artificial intelligent approach of producing combinational images by using GAN (Generative Adversarial Network). Han et al (2019) have proposed three approaches, problem-, similarity-and inspiration-driven, which can produce combinational creative ideas. In the study, an idea is regarded as an object or the concept of an object.…”
Section: Iced19mentioning
confidence: 99%
“…Here, a noun can refer to a single noun words (such as 'cup') as well as a noun phrase (such as a 'coffee cup'). The problem-driven approach indicates that combinational creativity is driven by design problems (Han et al, 2019). A design problem is described as the gap between the existing situation of an object and its target (Taura and Nagai, 2013), while solving a design problem is to explore ideas, known as problem-solving ideas that can bridge the gap.…”
Section: Iced19mentioning
confidence: 99%
See 2 more Smart Citations